KONTRIBUSI HUKUM ISLAM TERHADAP KOMPILASI HUKUM POSITIF DI INDONESIA - Rifki Kader; Nur Hasan; Abd Wafi (Jurnal Hikmatina, 2022)
Compilation of Islamic Law, is discuss aspects of Islamic law in Indonesia. This discussion complex matter even though occupies an important position in life of the nation today. Formulation of the problem is how to regulate Islamic Law in the Compilation of Islamic Law in Indonesia and how the position of the Compilation of Islamic Law in Positive Law in Indonesia. The position of the research is to determine the arrangement of Islamic Law in the Compilation of Islamic Law and to determine the position of the Compilation of Islamic Law in Positive Law in Indonesia. This type of research is normative, using descriptive analysis of library reasearch, primary legal materials, secondary legal materials and tertiary legal materials. The legal analysis method is normative juridical. The result was success in compiling the book Compilation of Islamic Law as a guide for the Muslim community in Indonesia and a reference for judges in the Religious Courts. Islamic law is regulated in three books Compilation of Islamic Law which contains Marriage Law, Inheritance Law and Endowment Law. The position of the Compilation of Islamic Law is recognized as one of the Positive Laws applicable in Indonesia based on Presidential Instruction No. 1 of 1991.